Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the Fourth ACM International Conference on Web Search and Data Mining 2011
DOI: 10.1145/1935826.1935925
|View full text |Cite
|
Sign up to set email alerts
|

The tube over time

Abstract: Understanding content popularity growth is of great importance to Internet service providers, content creators and online marketers. In this work, we characterize the growth patterns of video popularity on the currently most popular video sharing application, namely YouTube. Using newly provided data by the application, we analyze how the popularity of individual videos evolves since the video's upload time. Moreover, addressing a key aspect that has been mostly overlooked by previous work, we characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(31 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…In Crane and Sornette (), an epidemic model was defined to prove that viewing activity on YouTube can be explained by different factors, for example, new popular topics. A later study also found that the popularity of videos can be predicted by, among other factors, the occurrence of external events; for example, the video being massively posted in other online social networks and blogs (Figueiredo, Benevenuto, & Almeida, ). The impact of similar events, defined with data from Google Trends, was also analyzed in Wikipedia, concluding that trending topics notably affect the popularity of articles (Ratkiewicz, Flammini, & Menczer, ).…”
Section: Previous Researchmentioning
confidence: 93%
“…In Crane and Sornette (), an epidemic model was defined to prove that viewing activity on YouTube can be explained by different factors, for example, new popular topics. A later study also found that the popularity of videos can be predicted by, among other factors, the occurrence of external events; for example, the video being massively posted in other online social networks and blogs (Figueiredo, Benevenuto, & Almeida, ). The impact of similar events, defined with data from Google Trends, was also analyzed in Wikipedia, concluding that trending topics notably affect the popularity of articles (Ratkiewicz, Flammini, & Menczer, ).…”
Section: Previous Researchmentioning
confidence: 93%
“…The rapid development of the Internet results in the availability of a huge amount of data with time information, making it possible to study the popularity dynamic of the online content. It was found that the popularity of various pieces of content on the Web, like news [ 2 ], Twitter [ 3 ], blog posts [ 4 ], videos [ 5 , 6 ], posts in online discussion forums [ 7 ] and product reviews [ 8 ], vary significantly on temporal scales. In this context, the early identification of the eventual popular content becomes an important problem [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other research has found that "videos tend to get most of their views much earlier in their lifetimes" (Figueiredo, Benevenuto & Almeida, 2011). The research also found that "search and internal YouTube mechanisms, such as lists of related videos, are key mechanisms to attract users to the videos" which is significant to understand in order to maximise user engagement, as this would not occur at all if users could not reach the video itself.…”
Section: Related Workmentioning
confidence: 93%